2013
DOI: 10.3390/ijms14047140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Opuntia humifusa Supplementation and Acute Exercise on Insulin Sensitivity and Associations with PPAR-γ and PGC-1α Protein Expression in Skeletal Muscle of Rats

Abstract: This study examined whether Opuntia humifusa (O. humifusa), which is a member of the Cactaceae family, supplementation and acute swimming exercise affect insulin sensitivity and associations with PPAR-γ and PGC-1α protein expression in rats. Thirty-two rats were randomly divided into four groups (HS: high fat diet sedentary group, n = 8; HE: high fat diet acute exercise group, n = 8; OS: 5% O. humifusa supplemented high fat diet sedentary group, n = 8; OE: 5% O. humifusa supplemented high fat diet acute exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Similar to our present study, Kang et al [17] reported that 8 weeks of O. humifusa supplementation increased PPAR-γ protein expression in a rat model. We suggest that increased PPAR-γ protein expression in the present study occurred through increased PGC-1α, which is a co-activator of PPAR-γ, due to intake of calcium-rich O. humifusa.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our present study, Kang et al [17] reported that 8 weeks of O. humifusa supplementation increased PPAR-γ protein expression in a rat model. We suggest that increased PPAR-γ protein expression in the present study occurred through increased PGC-1α, which is a co-activator of PPAR-γ, due to intake of calcium-rich O. humifusa.…”
Section: Discussionsupporting
confidence: 92%
“…The use of animal models with diet-induced obesity helped to evaluate the nutritional values and some biological parameters of cactus seed supplements [ 99 , 100 ], dehydrated O. ficus-indica cladodes [ 101 , 102 ], or a combination of pre-Hispanic Mexican diet including nopal and nopal seeds [ 103 ] on rat models. These studies have shown that supplementation of diet with O. ficus-indica seed powder may have a favorable effect on the serum lipid profile and glucose, linked with beneficial effects on atherosclerosis, diabetes, and obesity [ 99 , 100 ].…”
Section: Biological and Medical Properties Of Opuntia mentioning
confidence: 99%
“…These studies have shown that supplementation of diet with O. ficus-indica seed powder may have a favorable effect on the serum lipid profile and glucose, linked with beneficial effects on atherosclerosis, diabetes, and obesity [ 99 , 100 ]. It exerts a favorable impact on insulin sensitivity through the regulation of genes involved in adipocyte differentiation [ 102 ], it attenuates hepatic steatosis in obese Zucker (fa/fa) rats [ 101 ], and it decreases metabolic and cognitive abnormalities and gut microbiota dysbiosis caused by a high-fat diet in rats [ 103 ]. To determine the metabolic effect of an O. ficus-indica extract on a mouse model of diet-induced obesity [ 104 ], the extract was added to a high-fat diet and administered to mice for 12 weeks.…”
Section: Biological and Medical Properties Of Opuntia mentioning
confidence: 99%
“…Recently, it has been shown to have antifungal [23] and anticancer [24,25] properties, as well as to improve insulin sensitivity [26] and increase bone density [27]. The objective of this study was to analyze the possible anti-asthmatic effects of O. humifusa and their mechanisms.…”
Section: Introductionmentioning
confidence: 99%